1983
DOI: 10.1111/j.1365-2125.1983.tb02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chloroquine and primaquine on antipyrine metabolism.

Abstract: 1 The effects of two antimalarial drugs, chloroquine and primaquine on antipyrine kinetics and metabolism have been studied in volunteers. 2 Chloroquine (250 mg) given 2 h before antipyrine (600 mg orally) had no effect on salivary kinetics of antipyrine or on the urinary recovery of metabolites. Primaquine (45 mg) given 2 h before antipyrine (300 mg orally), increased antipyrine half-life (calculated from 0-24 h) from 12.7 + 3.2 (mean + s.d.) to 25.3 + 3.9hand decreased clearance from3.01 + 0.67 to 1.32 + 0.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
2

Year Published

1985
1985
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 21 publications
2
13
2
Order By: Relevance
“…It has been shown previously that PQ (45 mg) inhibits the metabolism of antipyrine in man (Back et al, 1983a), as seen by an increase in the half-life of antipyrine elimination, and by a decrease in the clearance to metabolites following PQ administration. In contrast to this finding, CQ (250 mg) was found to have no significant effect on antipyrine metabolism in man.…”
Section: -Bis(trifluoromethyl)-4-quinolinemethanoli Is a New Antimalmentioning
confidence: 88%
“…It has been shown previously that PQ (45 mg) inhibits the metabolism of antipyrine in man (Back et al, 1983a), as seen by an increase in the half-life of antipyrine elimination, and by a decrease in the clearance to metabolites following PQ administration. In contrast to this finding, CQ (250 mg) was found to have no significant effect on antipyrine metabolism in man.…”
Section: -Bis(trifluoromethyl)-4-quinolinemethanoli Is a New Antimalmentioning
confidence: 88%
“…It has recently been shown that primaquine is a potent inhibitor of mixed function oxidase (M.F.O.) activity in both animals and man (Back et al, 1983a(Back et al, 1983bMihaly et al, 1985b).…”
Section: Introductionmentioning
confidence: 99%
“…The propensity of most antimalarial drugs to inhibit hepatic drug metabolizing enzymes had previously been reported in various studies (Back et al, 1983a;Back et al, 1983b;Mihaly et al, 1985;Riviere and Back, 1985;Na-Bangchang et al, 1992). Clinically relevant drug interaction was of a great concern when PQ is to be given concurrently with other antimalarial drugs.…”
Section: Referencementioning
confidence: 95%
“…The propensitity of such pharmacokinetic interaction has been raised when PQ is given at repeated dosing (auto-inhibition of hepatic drug metabolism) as well as in combination with other antimalarial drugs as a tissue schizontocide or gametocytocide. Previous studies demonstrated the potential of PQ as a potent inhibitor of cytochrome P450 in both animals and humans (Back et al, 1983a;Back et al, 1983b;Mihaly et al, 1985;Na-Bangchang et al, 1992). It is thought that the synergistic effects on radical curative activity between PQ and the standard blood schizontocidal antimalarial drugs CQ and quinine (Alving et al, 1980) could be linked to these pharmacokinetic drug interactions (cytochrome P450 inhibition) which result in elevated plasma concentrations of both CQ and quinine.…”
Section: General Pharmacokinetic Propertiesmentioning
confidence: 99%
See 1 more Smart Citation